Toksisitas Aktinobakteri ATS-7 Asal Tanah Stasiun Penelitian Soraya Kawasan Ekosistem Leuser Berdasarkan Waktu dan Suhu Inkubasi - Dhea Amanda Adryan; Lenni Fitri; Fauziah Fauziah (Jurnal Bioleuser, 2025)
Actinobacteria are prokaryotic microorganisms that have a morphological form resembling filamentous fungi, and are generally found in soil and have many beneficial potentials. This study aims to determine the effect of the toxicity test of actinobacteria ATS-7 from the soil of the Soraya Research Station based on incubation time and temperature. Toxicity testing was carried out using the Brine Shrimp Lethality Test (BSLT) method to obtain the LC₅₀ value. The toxicity test was carried out by calculating the number of dead Artemia salina larvae. The results of the toxicity test showed that the ATS-7 isolate at a temperature of 32ºC which was shaken for 5 days with an LC₅₀ value of 77.49 ppm, 10 days with an LC₅₀ value of 62.88 ppm, 15 days with an LC₅₀ value of 53.70 ppm. This temperature has very high toxicity activity, and has an LC₅₀ value of <100 ppm, meaning that the incubation time at 32ºC greatly affects the toxicity test and is very toxic.